Study of the basic chemical composition and some biological compounds of the flowers of Cercis siliquastrum L. - Khaddam, Shaza (Latakia University Journal -Biological Sciences Series, 2025)
In this research, the chemical components of the flowers of the Syrian Zamzariqa plant were studied, which were collected from the areas of Salnfa and Kasab in the countryside of Lattakia city. The moisture content in the flowers was estimated and was 1.1 ± 71.45%, and the remaining components were estimated. The protein content was 0.25 ± 5.2%, the lipids 0.76 ± 1.17%, the fibers 0.33 ± 12.32%, the ash content 0.1 ± 2.3%, the total soluble sugars 0.21 ± 4.47%, and the reducing sugars 0.12 ± 2.97%. The total polyphenols in the aqueous extract of the dry flowers were estimated on the basis of mg of gallic acid and were 0.02 ± 35.7%. As for the antioxidant capacity, it was 0.13 ± 79.81 according to the DPPH Di Phenyl Picryl Hdrazyl method. The essential oil of the flowers was extracted and its components were studied using gas chromatography GC-MS.